Genetic diversity, forensic characteristics and phylogenetic analysis of the Qiongzhong aborigines residing in the tropical rainforests of Hainan Island via 19 autosomal STRs. (19th May 2021) - Wang, Fenfen; Du, Zhengming; Han, Bingbing; Cao, Shengping; Fu, Fangshu; Luo, Zhenming; Mu, Ziqing; Chen, Jirui; Qiu, Pingming; Fan, Haoliang
Abstract: Background: The genetic landscape of the Qiongzhong aborigines, who reside in "the Heart of Hainan, " is still unclear. The Goldeneye™ DNA ID System 20 A is available for forensic and population genetics applications. Aim: To obtain genetic polymorphisms of 19 autosomal STR loci in the Qiongzhong aborigines, and to explore the genetic relationships with a total of 69, 132 people from forty-five populations. Subjects and methods: Genotype data on 19 autosomal STRs were collected from 724 Qiongzhong aborigines and phylogenetic relationships were conducted by multidimensional scaling analysis (MDS), principal component analysis (PCA) and neighbor-joining (N-J) phylogenetic tree construction. Results: No evidence of deviation from Hardy-Weinberg equilibrium was identified. A total of 233 distinct alleles were observed with allele frequencies ranging from 0.0007 to 0.5375. The combined power of discrimination (CPD) and combined power of exclusion (CPE) for the 19 autosomal STR loci were 1–8.28 × 10 –34 and 0.999999987, respectively. Conclusion: Our phylogenetic results demonstrated that (a) the populations of Southeast Asian countries have thorough integrations with southern China in terms of ethnicity and genetics due to long-term cultural and trade exchanges, and (b) based on genetic and linguistic analysis, the Qiongzhong aborigines have a close relationship with Fujian Han Chinese. Highlights: The STR landscape of Qiongzhong aborigines inhabited in Hainan tropical rainforests was depicted by 19 autosomal STRs. A total of 69, 132 people from forty-five populations were selected for a more extensive examination of genetic similarities and differences by multivariate statistical methods (MDS, PCA and N-J tree construction). The genetic analyses indicated that the populations of Southeast Asian countries are very genetically close to southern Chinese populations. From the genetic and linguistic perspective, the Qiongzhong aborigines have a close relationship with Han Chinese from Fujian Province.